Relationships reduce risks for child maltreatment: Results of an experimental trial of Infant Mental Health Home Visiting - Julian, Megan M.; Riggs, Jessica; Wong, Kristyn; Lawler, Jamie M.; Brophy-Herb, Holly E.; Ribaudo, Julie; Stacks, Ann; Jester, Jennifer M.; Pitzen, Jerrica; Rosenblum, Katherine L.; Muzik, Maria; , on behalf of The Michigan Collaborative for Infant Mental Health Research (MCIMHR) (Frontiers in Psychiatry, 2023)
Background Research examining the effectiveness of home visiting programs that reduce child maltreatment or associated risks yield mixed findings; some find positive significant impacts on maltreatment, whereas others find small to no effects. The Michigan Model of Infant Mental Health Home Visiting (IMH-HV) is a manualized, needs-driven, relationship-focused, home-based intervention service that significantly impacts maternal and child outcomes; the effect of this intervention on child maltreatment has not been sufficiently evaluated. Objective The current study examined associations between treatment and dosage of IMH-HV and child abuse potential in a longitudinal, randomized controlled trial (RCT). Participants and setting Participants included 66 mother-infant dyads (Mother M age = 31.93 years at baseline; child M age = 11.22 months at baseline) who received up to 1 year of IMH-HV treatment (Mdn = 32 visits) or no IMH-HV treatment during the study period. Methods Mothers completed a battery of assessments including the Brief Child Abuse Potential Inventory (BCAP) at baseline and at the 12-month follow-up assessment. Results Regression analyses indicated that after controlling for baseline BCAP scores, those who received any IMH-HV treatment had lower 12-month BCAP scores compared to those who received no treatment. Additionally, participation in more visits was associated with lower child abuse potential at 12 months, and a reduced likelihood of scoring in the risk range. Conclusion Findings suggest that greater participation in IMH-HV is associated with decreased risk for child maltreatment 1 year after initiating treatment. IMH-HV promotes parent-clinician therapeutic alliance and provides infant-parent psychotherapy which differentiate it from traditional home visiting programs.